<em>the</em><em> </em><em>fir</em><em>st</em><em> </em><em>thing</em><em> </em><em>you</em><em> </em><em>nee</em><em>d</em><em> </em><em>to</em><em> </em><em>do</em><em> </em><em>is</em>
<em>div</em><em>ide</em><em> </em><em>the</em><em> </em><em>who</em><em>le</em><em> </em><em>equ</em><em>ation</em><em> </em><em>by </em><em>rt</em><em> </em><em>as</em><em> </em><em>sh</em><em>own</em><em> </em><em>bel</em><em>ow</em>
<em>
</em>
<em>then</em><em> </em><em>you</em><em> </em><em>cance</em><em>l</em><em> </em><em>ou</em><em>t</em><em>.</em><em> </em><em>leav</em><em>ing</em>
<em>
</em>
<em>which</em><em> </em><em>is</em><em> </em><em>the</em><em> </em><em>sam</em><em>e</em><em> </em><em>as</em>
<em>
</em>
The answer to question above is 0.0000593
Maybe this will help! (:
https://youtu.be/1wPJfzStBqE
<span>3x+ 2y+7 -5x+7y
= -2x + 9y + 7
hope it helps</span>
Answer:
f(-4) = -18
Step-by-step explanation:
f(-4) means x = - 4
So Plug in x = - 4 into f(x) = 3x - 6
f(-4) = 3(-4) - 6
= -12 - 6
= -18
So
f(-4) = -18